Implications of Hydrocephalus on FDG-PET Statistical Parametric Mapping Analysis in Neurodegenerative Disease Evaluation - Ricaurte-Fajardo, Andres; Franceschi, Ana M.; D’Angelo, Debra; McCalla, Aliah; Salgado, Miran; Hamed, Moath; Intorcia, Brielle; Wisherop, Carlyn; Keil, Samantha A.; Nordvig, Anna S.; Osborne, Joseph R.; Chiang, Gloria C.; et al. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: FDG-PET is critical in the diagnosis of neurodegenerative disease. Quantitative analysis with statistical parametric mapping (SPM) has been shown to improve the diagnostic accuracy of FDG-PET and has been incorporated in clinical workflows. This study aimed to assess the effects of hydrocephalus on the accuracy of FDG-PET SPM analysis, focusing on the cingulate gyrus regions, which are of particular interest in dementia evaluation and are adjacent to the lateral ventricles.MATERIALS AND METHODS: In this retrospective institutional review board–approved study, patients who underwent brain FDG-PET/CT or PET/MRI were evaluated. Inclusion criteria were a clinical history of cognitive impairment/suspected neurodegenerative disease and MRI evidence of communicating hydrocephalus. Region-specific z scores for the anterior, middle, and posterior cingulate gyri (ACG, MCG, PCG), as well as for the cerebellum were generated using SPM analysis. Blinded expert qualitative assessment was performed for each anatomic region. κ coefficients were computed to evaluate the agreement between quantitative and qualitative results. Paired nonparametric t tests assessed z score differences between the cingulate and cerebellar regions.RESULTS: The study included 48 patients (17 women; mean age, 76 years). SPM analysis found significantly lower cingulate z scores compared with the cerebellum [−4.3 (ACG), −6.9 (MCG), and −3.2 (PCG), −1.2 (cerebellum) P < .0001]. Similar results were observed in the signed-rank tests comparing cingulate regions with the cerebellum [ACG, −3.2 (SD, 2.1); MCG, −5.7 (SD, 3.6); PCG, −1.9 (SD, 2.4), P < .001 for all 3 cingulate regions]. κ coefficients indicated poor agreement between SPM and qualitative assessments (κ = 0.05–0.19, P values = .078–.479).CONCLUSIONS: Our study highlights hydrocephalus as an important pitfall of FDG-PET SPM, particularly when analyzing the cingulate regions, integral to the clinical evaluation of dementia. Awareness of this pitfall can improve diagnostic accuracy and thus improve clinical outcomes in this growing patient population.ACGanterior cingulate gyrusCBLcerebellumMCGmiddle cingulate gyrusNPHnormal pressure hydrocephalusPCGposterior cingulate gyrusSPMstatistical parametric mappingSUVstandard uptake values